Reaction Conditions for the Isomerization and Epimerization of Lactose with a Mutant Cellobiose 2-Epimerase - Vera-Vera, C (Academic Press, 2025)
A sound alternative to the chemical synthesis of lactulose is the direct isomerization of lactose using cellobiose 2-epimerase as catalyst. In this reaction, epilactose, a potential prebiotic, is synthesized along with lactulose. A new mutant cellobiose 2-epimerase from Caldicellulosiruptor saccharolyticus (CsCE H349N) was characterized kinetically and evaluated in the reaction of lactose conversion into lactulose and epilactose. Temperature, pH, initial lactose concentration and enzyme/substrate ratio (E/S) were evaluated as operational variables. The operational response parameters lactulose and epilactose yield and productivity, and lactulose selectivity were significantly affected by the E/S, being possible to drive the reaction into the formation of epilactose or lactulose. Lactulose yield of 0.677 ± 0.0121 g/g with only 0.095 ± 0.003 g/g of epilactose yield was obtained, which is one of the highest lactulose yield reported without the addition of complexing agents, like boric acid, which are hard to remove from the product stream. If the objective is pure epilactose production, this can be achieved at low E/S ratios, where epimerization is privileged over isomerization, in which case a maximum epilactose yield of 0.256 ± 0.0048 g/g was obtained with no lactulose or other unwanted products being formed. © 2025 The Author(s)